2022
DOI: 10.1097/shk.0000000000001938
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injury-Induced Extracellular Vesicle Production and Characteristics

Abstract: Extracellular vesicles (EVs) are nano-sized membrane-bound particles containing biologically active cargo molecules. The production and molecular composition of EVs reflect the physiological state of parent cells, and once released into the circulation, they exert pleiotropic functions via transferring cargo contents. Thus, circulating EVs not only serve as biomarkers, but also mediators in disease processes or injury responses. In the present study, we performed a comprehensive analysis of plasma EVs from bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…We and others have found that circulating EV levels change after burn injury and participate in burn pathology. After a severe burn injury, there are increased numbers of circulating plasma EVs ( 6 , 15 , 16 ). Furthermore, there is a positive correlation between the level of circulating EVs and severity of burn injury, with increased EV concentrations corresponding to increases in percentage of total body surface area burn, and these concentrations correlate with postburn sepsis, wound infection, and admission to intensive care units ( 15 , 16 ).…”
Section: Extracellular Vesicles As Mediators In Traumamentioning
confidence: 99%
See 4 more Smart Citations
“…We and others have found that circulating EV levels change after burn injury and participate in burn pathology. After a severe burn injury, there are increased numbers of circulating plasma EVs ( 6 , 15 , 16 ). Furthermore, there is a positive correlation between the level of circulating EVs and severity of burn injury, with increased EV concentrations corresponding to increases in percentage of total body surface area burn, and these concentrations correlate with postburn sepsis, wound infection, and admission to intensive care units ( 15 , 16 ).…”
Section: Extracellular Vesicles As Mediators In Traumamentioning
confidence: 99%
“…After a severe burn injury, there are increased numbers of circulating plasma EVs ( 6 , 15 , 16 ). Furthermore, there is a positive correlation between the level of circulating EVs and severity of burn injury, with increased EV concentrations corresponding to increases in percentage of total body surface area burn, and these concentrations correlate with postburn sepsis, wound infection, and admission to intensive care units ( 15 , 16 ). Inhalation injury due to smoke or chemical fume inhalation often occurs at the time of burn injury and increases morbidity and mortality for patients ( 14 ).…”
Section: Extracellular Vesicles As Mediators In Traumamentioning
confidence: 99%
See 3 more Smart Citations